Retest reliability of repetitive transcranial magnetic stimulation over the healthy human motor cortex: a systematic review and meta-analysis - Kanig, Carolina; Osnabruegge, Mirja; Schwitzgebel, Florian; Litschel, Karsten; Seiberl, Wolfgang; Mack, Wolfgang; Schoisswohl, Stefan; Schecklmann, Martin (Frontiers in Human Neuroscience, 2023)
Repetitive transcranial magnetic stimulation (rTMS) is used to induce longlasting changes (aftereffects) in cortical excitability, which are often measured via single pulse TMS (spTMS) over the motor cortex eliciting motor evoked potentials (MEPs). RTMS includes various protocols, such as theta burst stimulation (TBS), paired associative stimulation (PAS) and continuous rTMS with fixed frequency. Yet, subsequent aftereffects of rTMS are variable and seem to fail repeatability. We aim to summarize standard rTMS procedures regarding their test-retest reliability. Hereby, we consider influencing factors like methodological quality of experiments and publication bias.We conducted a literature search via PubMed latest in March 2023. Inclusion criteria were the application of rTMS, TBS or PAS at least twice over the motor cortex of healthy subjects with measurements of MEPs via spTMS as dependent variable. Exclusion criteria were measurements derived from the non-stimulated hemisphere, of non-hand muscles and by electroencephalography only. We extracted test-retest reliability measures and aftereffects from the eligible studies. With Rosenthal fail safe n, funnel plot and asymmetry test we examined the publication bias and accounted for influential factors like methodological quality of experiments measured with a standardized checklist.Results: 15 studies were identified that investigated test-retest reliability of rTMS protocols in a total of 291 subjects. Reliability measures, i.e., Pearson's r and intraclass correlation coefficient applicable from 9 studies, were mainly in the small to moderate range with two experiments indicating good reliability of 20 Hz rTMS (r = 0.543) and iTBS (r = 0.55). Aftereffects of rTMS procedures seem to follow the heuristic of respective inhibition or facilitation depending on the protocols' frequency and application pattern. There was no indication of publication bias and influence of methodological quality or other factors on reliability of rTMS.Reliability of rTMS appears to be small to moderate overall. Due to a limited amount of studies reporting test-retest reliability values and heterogeneity of dependent measures, we cannot provide generalizable results. We could not identify any protocol as superior to the others.